The capabilities that count for early professional success in pharmacy: A case study of graduates, employer and course team perspectives - Tee, L.; Ferns, Sonia; Hughes, Jeff (2018)
© 2018 Deakin University. All rights reserved. This study gathered and analysed the perceptions of graduates, employers, and the course team regarding graduate capabilities required for early professional success in pharmacy and the extent to which these capabilities are demonstrated in new graduates. The Graduate Employability Indicator (GEI) surveys were administered online to gather stakeholders’ perceptions about the Bachelor of Pharmacy offered at a large Australian university. The GEI asks graduates the extent to which their course experience contributed to achievement of the capabilities, and asks employers and course teams about the extent to which new graduates demonstrated the capabilities. This study also assessed the incentives and disincentives of the course team for assisting to develop work-related skills, attributes and personal qualities. In total, 95 graduates, 109 employers and 42 members of the course team participated in the survey. The findings indicated that graduates preferred earlier professional placement in the course. Employers identified communication and professional skills as the most useful capabilities for new graduates. Members of the course team identified benefits to the students, industry and university as the main incentives for developing graduate employability. Both employers and course team members perceived the use of technology demonstrated by the graduates as important, however the graduates perceived this as much less important compared to other capabilities This study provided an evidence-based approach to engage the course team in curriculum renewal for the Bachelor of Pharmacy program. Data collected using the GEI tool provided valuable information for reshaping the curriculum structure.